Penerapan Teknik Relaksasi Otot Progresif pada Asuhan Keperawatan Pasien dengan Hipertensi - Halida Mubarokah; Yuanita Panma (AKPER Pasar Rebo, 2023)
Hypertension, known as the silent killer, is a world health problem with a high prevalence rate. Treatment of hypertension needs to be taken seriously to prevent complications that can reduce the patient's quality of life. The purpose of this study was to apply nursing care and progressive muscle relaxation techniques to hypertensive patients with a comprehensive nursing process approach. This research method uses a descriptive method with a case study approach accompanied by the application of evidence-based practices. Nursing care was carried out on a male patient, aged 58 years, with a medical diagnosis of hypertension. From the assessment, five nursing problems were obtained, namely high risk of decreased cardiac output, acute pain, risk of nutritional deficits, activity intolerance, and lack of knowledge. The implementation for nursing problems at high risk of decreased cardiac output is to perform progressive muscle relaxation techniques. The evaluation results showed a decrease in blood pressure from 172/90 mmHg on the first day to 142/85 mmHg on the third day. Progressive muscle relaxation techniques can be applied to hypertensive patients to lower blood pressure. Nurses can teach patients and families progressive muscle relaxation techniques to lower blood pressure.